RARE VASCULAR ANOMALY «ARTERIAL FORCEPS» AS A CAUSE OF OBSTRUCTION URETEROPELVIC JUNCTIONOF THE RIGHT KIDNEY - M. M. Batyushin; A. A. Kastanayan; I. S. Valueva (Вестник урологии, 2014)
The article describes a clinical case of right renal artery anomalies in the form of «arterial forceps». Patient S., 26 years have seen a university clinic for two years. Complained of heaviness in the right lumbar region, not associated with urination and stoped after taking antispasmodics (drotaverin). In urinalysis revealed no pathological changes, serum creatinine, glomerular filtration rate in the normal range. Palpation in the right flank found kidney, easily movable hand pressure, painless. Ultrasound during supine and standing were identified nephroptosis, yavivsheesya indication for endoscopic surgery nephropexy. However, after the operation the patient's condition has not improved. Pain intensified and gained position hue. The study was revealed complex malformation of the vascular bed of the right kidney . It has been found that the right renal artery divides into two long branches before entering the gates kidney then forward it again bifurcated branch of the upper and lower branches and the same before entering the gates, forming a compression pelvis and causing its dilation.